Saving and investment in South Africa: a causality study - Mngqibisa, Vuyisa (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2014)
This study aims to investigate the relationship between private saving and investment for South Africa using a Vector Error Correction Framework. Saving and investment are considered to be important factors for sustainable economic growth in the country, particularly as these variables have been recorded at significantly lower levels than those of other developing nations. By examining the direction of causality between saving and investment, the most suitable policy measures can be used in stimulating either savings or investment, and as a result aggregate growth. The study found a positive two-way causality to exist between these two variables, proving that both saving and investment-led policies are necessary in raising saving and investment levels. With the inclusion of credit extension as the third variable used to remove any variable bias, the study not only found credit extension to Granger cause private saving, but the reverse relationship was found to be present as well. This relationship was however found to be negative, confirming that lower borrowing constraints may have a negative effect on saving levels. The negative relationship between credit supply and private saving (substitution effect) proves that credit supply will only yield a positive result for savings if channelled through investment expenditure.
Keywords: Saving and investment -- South Africa; Investments -- South Africa; Credit -- South Africa; Finance, Personal -- South Africa; Portfolio management -- South Africa; Investment analysis -- South Africa; Error analysis (Mathematics)